2003
DOI: 10.1080/10640260390218666
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Eating in Female College Athletes: A Survey of Coaches

Abstract: The purpose of the present study was to gather information from coaches regarding their monitoring/management of athlete eating and weight, knowledge of nutritional health issues, availability of prevention/intervention services for athletes at their school, experience with athletes exhibiting symptoms of eating and body image disturbances, and their attitudes toward eating and weight in the sport. A total of 303 coaches (51% response rate) involved in six sports (i.e., gymnastics, swimming, basketball, softba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
2
22
1
5
Order By: Relevance
“…Another clear area of gendered results was with respect to attitudes and communication about menstrual irregularity, and in many ways it reflects previous findings of gender differences among collegiate coaches (Heffner et al, 2003;Sherman et al, 2005). Compared to female coaches, male coaches reported perceiving menstrual irregularity to be less harmful to health, believing that it was less important to ask athletes about menstrual irregularity, being less comfortable communicating with female athletes about the topic, and believing there to be less of an association between menstrual irregularity and issues of bone health.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Another clear area of gendered results was with respect to attitudes and communication about menstrual irregularity, and in many ways it reflects previous findings of gender differences among collegiate coaches (Heffner et al, 2003;Sherman et al, 2005). Compared to female coaches, male coaches reported perceiving menstrual irregularity to be less harmful to health, believing that it was less important to ask athletes about menstrual irregularity, being less comfortable communicating with female athletes about the topic, and believing there to be less of an association between menstrual irregularity and issues of bone health.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies of college coaches (Heffner et al, 2003;Sherman et al, 2005) have found differences between male and female coaches of female athletes in terms of attitudes and communication with athletes about disorders of the Female Athletes Triad. To our knowledge, the present study is the first to extend this analysis to high school coaches.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gender is one risk factor for ED among athletes, with female athletes especially at risk [7][8][9]. Another risk factor is the level of performance, with athletes at the highest levels of competition being at the highest risk [10][11][12]. Factors that contribute to risk, both environmental (e.g., the intense pressure to be thin) and attitudinal (e.g., persistence, perfectionist tendencies), are common in elite athletes [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 37% of U.S. college coaches indicated that amenorrhea was "normal." Further, coaches' behaviors may increase athletes' likelihood of developing EDs, such as by monitoring eating patterns, regularly weighing athletes and assessing body fat, and encouraging weight loss through food restriction and extra workouts (Heffner, Ogles, Gold, Marsden, & Johnson, 2003). Athletes may be particularly sensitive to, and influenced by, weight and body comments made by coaches (e.g., de Bruin, Oudejans, & Bakker, 2007).…”
Section: Identificationmentioning
confidence: 99%